2008
DOI: 10.1007/s00213-008-1270-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic caffeine exposure on adenosinergic modulation of the discriminative-stimulus effects of nicotine, methamphetamine, and cocaine in rats

Abstract: Rationale Adenosine receptors are involved in cocaine and methamphetamine discrimination and exposure to caffeine can affect behavioral effects of nicotine in rats. Objectives Here we investigated the relative involvement of adenosine A 1 and A 2A receptors in nicotine, cocaine, and methamphetamine discrimination, before and/or during chronic caffeine exposure. Materials and methods The nonselective adenosine receptor antagonist caffeine, the A 1 -receptor antagonist cyclopentyltheophylline (CPT), and the A 2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…One potential explanation is that there was a generalization between the effects of CAF and NIC, as reinstatement occurred with both conditions when combined with cues. This hypothesis is supported by findings showing that caffeine produced nicotine-like discriminative stimulus effects in a substitution task [63]. The interaction between caffeine, nicotine and nicotine-associated cues on relapse to nicotine use is important to our understanding of factors that maintain nicotine and tobacco use in humans; however, further exploration is needed the given conditioned reinforcement-enhancement effects of both drugs and the high rate of NIC and CAF co-use [62,64].…”
Section: Discussionmentioning
confidence: 87%
“…One potential explanation is that there was a generalization between the effects of CAF and NIC, as reinstatement occurred with both conditions when combined with cues. This hypothesis is supported by findings showing that caffeine produced nicotine-like discriminative stimulus effects in a substitution task [63]. The interaction between caffeine, nicotine and nicotine-associated cues on relapse to nicotine use is important to our understanding of factors that maintain nicotine and tobacco use in humans; however, further exploration is needed the given conditioned reinforcement-enhancement effects of both drugs and the high rate of NIC and CAF co-use [62,64].…”
Section: Discussionmentioning
confidence: 87%
“…Thus, repeated treatment or continuous exposure of caffeine has been shown to augment the psychomotor effects of cocaine or amphetamine, as measured with locomotor activity (Schenk et al 1990; Gassior et al 2000), turning behavior (Cauli et al 2003) and reward/drug-oriented behavior (Horger et al 1991; Jaszyna et al 1998). Using the drug-discrimination paradigm, Goldberg’s research group also demonstrated that continuous exposure to caffeine is associated with tolerance to the ability of A 1 but not A 2A receptor antagonists to potentiate the discriminative-stimulus effects of cocaine or amphetamine (Justinova et al 2009). Lastly, coadministration of caffeine or an A 2A receptor antagonist has been shown to potentiate cocaine-induced sensitization of psychomotor activity (Filip et al 2006; Prieto et al 2015).…”
Section: The Real Danger: Caffeine Potentiates the Addictive And Toximentioning
confidence: 99%
“…As customary in most coffee consumers, long-term intake of caffeine leads to the development of tolerance to some of its acute effects by mechanisms not yet fully understood, although most studies found an increased number of A 1 , but not A 2A receptors, in several brain areas (Jacobson et al, 1996). Chronic caffeine intake has also been associated with increased behavioral effects of some drugs of abuse, for example, amphetamine and cocaine (Gasior et al, 2000;Justinova et al, 2009). THC is the main psychoactive constituent of the cannabis plant, which is consumed recreationally or used for medicinal purposes; it mainly activates cannabinoid CB 1 receptors in the central nervous system to produce motor-and cognitive-disrupting effects (see Pertwee, 2008).…”
mentioning
confidence: 99%